Field emission from oriented tin oxide rods - Deshpande, A. C.; Koinkar, Pankaj M.; Ashtaputre, S. S.; More, Mahendra A.; Gosavi, S. W.; Godbole, P. D.; Joag, Dilip S.; Kulkarni, S. K. (Thin Solid Films, 2006)
Tin oxide (SnO2) films were grown on silicon substrates by a wet chemical route. It was found from scanning electron microscopy investigations that oriented SnO2 rods normal to the substrates were obtained. Field emission studies were carried out in diode configuration in an all metal ultra high vacuum chamber at a base pressure similar to 1.33 x 10(-8) mbar. The `onset' field required to draw 0.1 mu A/cm(2) current density from the emitter cathode was found to be similar to 3.4 V/mu m for SnO2 rods. The field emission current and applied field follows the Folwer-Nordheim relationship in low field regime. The observed results indicate that the field emission characteristics of chemically grown SnO2 structures are comparable to the vapor grown nanostructures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: field emission; microstructures; scanning electron microscopy; tin oxide

Field emission investigations of RuO2-doped SnO2 wires - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Applied Surface Science, 2007)
Field emission studies of a bunch and a single isolated RuO2:SnO2 wire have been performed. A current density of 5.73 x 10(4) A/cm(2) is drawn from the single wire emitter at an applied field of 8.46 x 10(4) V/mu m. Nonlinearity in the Fowler-Nordheim (F-N) plot has been observed and explained on the basis of electron emission from both the conduction and the valence bands of the semiconductor. The current stability recorded at the preset value of 1.5 LA is observed to be good. Overall the high emission current density, good stability and mechanically robust nature of the RuO2:SnO2 wires offer advantages as field emitters for many potential applications. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emission; field enhancement factor; RuO2; SnO2

Field emission investigation of single Fe-doped SnO2 wire - Bhise, Ashok B.; Late, Dattatray J.; Sathe, Bhaskar R.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Solid State Sciences, 2009)
Tin oxide submicronwires doped with Fe element were prepared by the thermal evaporation method. Morphological and structural characterizations revealed wires with sub micron size and crystalline in nature. The field electron emission from the single Fe:SnO2 wire was carried out in conventional field emission microscope. The Fowler-Nordheim plot obtained from I-V characteristics of the wire showed a linear behavior typical that of metal. The field enhancement factor estimated from the slope of the F-N plot is 7455 cm(-1), indicating that the field emission is from nanometric features of the emitter. A current density of 10 A/cm(2) has been obtained at an applied field of 4.845 x 10(3) V/mu m. The field emission current-time record at a current level of 1 mu A for more than 3 h duration is promising for various field emissions based applications. (C) 2009 Published by Elsevier Masson SAS.
Keywords: Current stability; Fe doped; field emission; SnO2

Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Fowler-nordheim plot behavior and mechanism of field electron emission from ZnO tetrapod structures - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (ACS Nano, 2010)
Field emission measurements of current-voltage characteristics are reported for tetrapod structures of ZnO. The nonlinear Fowler-Nordheim (FN) plot is analyzed according to a model of calculation based on saturation of conduction band current and predominance of valence band current at high-field values. The simulated FN plot exhibits similar features to those observed experimentally. The model of calculation suggests that the slope variation of the FN plot, in the high-field and low-field regions, does not depend on the magnitude of saturation. Instead, it is a characteristic of the energy band structure and voltage-to-barrier-field conversion factor of the emitting material.
Keywords: field emission; Fowler-Nordheim plot; Nanostructures; nonlinearity; ZnO

High current density, low threshold field emission from functionalized carbon nanotube bucky paper - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Late, Dattatray J.; Chavan, Padmakar G.; Sheini, Farid J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2010)
Field emission studies of bucky paper of multiwalled carbon nanotubes (MWNTs), prepared after microwave (MW) assisted acid functionalization are reported along with a comparison with that of ``as-grown'' sample. MW treated bucky papers reveal an interesting linear field emission behavior in Fowler-Nordheim plot. The field emission currents at preset value are found to be remarkably stable over a period of more than 3 h sustaining current densities of 4.9 mA/cm(2) and 8.5 mA/cm(2) for ``as-grown'' and functionalized sample, respectively. The enhancement in the field emission due to functionalization has been discussed in terms of tip opening and defect induced charge transport caused by intershell and intertubular interaction. (C) 2010 American Institute of Physics. [doi:10.1063/1.3479049]
Keywords: Carbon nanotubes; current density; field emission; fullerenes

Field emission studies of silver nanoparticles synthesized by electron cyclotron resonance plasma - Purohit, Vishwas; Mazumder, Baishakhi; Bhise, Ashok B.; Poddar, Pankaj; Joag, Dilip S.; Bhoraskar, S. V. (Applied Surface Science, 2011)
Field emission has been studied for silver nanoparticles (25-200 nm), deposited within a cylindrical silver target in an electron cyclotron resonance (ECR) plasma. Particle size distribution was controlled by optimum biasing voltages between the chamber and the target. Presence of non-oxidized silver was confirmed from the X-Ray diffraction analysis; however, thin protective layer of oxide was identified from the selective area electron diffraction pattern obtained with transmission electron microscopy. The silver nanoparticles were seen to exhibit hilly pointed like structures when viewed under the atomic force microscopy (AFM). The emissive properties of these particles were investigated by field emission microscopy. It is found that this technique of deposition is ideal for formation of nanoparticles films on different substrate geometries with size controllability as well as its application to emission devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cold plasma; field emission; Nanoparticles; thin film

Synthesis of Cu-ZnO and C-ZnO nanoneedle arrays on zinc foil by low temperature oxidation route: effect of buffer layers on growth, optical and field emission properties - Jamali-Sheini, Farid; Patil, K. R.; Joag, Dilip S.; More, Mahendra A. (Applied Surface Science, 2011)
Different densities of ZnO nanoneedle films have been prepared by pre-coated zinc foils with thin layer of copper and carbon followed by thermal oxidation at 400 degrees C in air. The X-ray diffraction patterns show well defined peaks, which could be indexed to the wurtzite hexagonal phase of ZnO. The scanning electron microscope images clearly reveal formation of ZnO needles on the entire substrate surface. The X-ray photoelectron spectroscopy studies indicate that Cu and C ions are incorporated into the ZnO lattice. Photoluminescence studies evaluate different emission bands originated from different defect mechanism. From the field emission studies, the threshold field, required to draw emission current density of similar to 100 mu A/cm(2), is observed to be 2.25 V/mu m and 1.57 V/mu m for annealed zinc foil pre-coated with copper and carbon, respectively. The annealed film with copper layer exhibits good emission current stability at the pre-set value of similar to 100 mu A over a duration of 4 h. The results show that buffer layer is an important factor to control the growth rate, resulting in different density of ZnO needles, which leads to field emission properties. This method may have potential in fabrication of electron sources for high current density applications. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Buffer layer; Carbon; Copper; field emission; Nanoneedle; ZnO

CdS nanowires: ultra-long growth and enhanced field emission properties - Chavan, Padmakar G.; Kashid, Ranjit V.; Badhade, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Vaccum, 2014)
Here, we report the synthesis of ultra-long CdS nanowires with aspect ratio similar to 8 x 10(4) by simple route of thermal evaporation technique. A change in the vertical arrangement of quartz boats leads in to the synthesis of ultra-long CdS nanovvires via high degree of condensation. This technique is seen to be cost effective and easy. The growth of the nanowires is found to be increased very rapidly from few micrometers to few millimeters. The possible reason for the growth of the ultra-long CdS nanowires is discussed in detail. The turn-on field defined for the current density of similar to 0.1 mu A/cm(2) has been found to be similar to 1.4, 1.45, 1 and 0.17 V/mu m for specimen A, B, C and D (specimens A-D, synthesized by variation in synthesis parameters) respectively. The turn-on field of the specimen D (similar to 0.17 V/mu m) is found to be quite superior than the value reported for other CdS nanoforms which is very remarkable. Simple way of bulk fabrication leads to the low turn-on value which indicates a possible use of the present emitter in the micro/nanoelectronics devices. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Current stability; field emission; synthesis

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
27th International Vacuum Nanoelectronics Conference (IVNC), Engelberg, SWITZERLAND, JUL 06-10, 2014
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Photosensitive field emission study of SnS2 nanosheets (27th International Vacuum Nanoelectronics Conference ) - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (2014 27TH International Vacuum Nanoelectronics Conference (IVNC), 2014)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to Field Emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solution are used. The FE study is carried out in all metal Ultra High Vacuum (UHV) chamber in planar diode configuration at a base pressure of similar to 10(-8) torr. A maximum current density of 110 mu A/cm(2) was attainable. The turn on field required to draw a current density of 1 mu A/cm(2) is found to be 2.6 V/mu m. A separate study was carried out to investigate the photosensitivity of the emitter by illuminating the specimen under visible light. In dark, the FN plot is non-linear, indicative of semiconductor nature of the emitter. However, on illumination, the FN plot is observed to be linear. This remarkable change can be explained by the photoconductivity imparted on illumination. The field at the tip is high in presence of light, than in dark, due to enhanced conductivity. It is also observed that on switching ON the light, the FE current increases almost instantaneously. Repetitive switching is observed at a fixed applied voltage, generating current pulses. The visible light soaking of the sample is carried out by illuminating the lamp for more than 100 minutes, where the current seems to saturate. On switching off the lamp the emission current decayed almost to its initial value exponentially. The photosensitivity has been studied for different wavelengths in the visible spectra. The maximum photosensitive field emission is observed for green filter. With this photoresponse, it is envisaged that SnS2 nanosheets are a potential candidate for optoelectronic applications of field emitters.
Keywords: field emission; photosensitivity; Photoswitching